The RelationshipBetween Online Game Exposure and Sleep Quality in Students at SMAN 13 Medan City - Azzahra, Syifa Nadya; Nuralita, Nanda Sari (Buletin Farmatera, 2025)
Abstract: Playing online games done during activities at night can come at the expense of sleep. The quality of a person's sleep is influenced by several aspects such as the duration of sleep, the time it takes to fall asleep, the frequency of waking up, and the level of sleep deprivation. Sleep disorders are a decrease in sleep quality that occurs due to daily activities, especially in adolescents. The quality of sleep can continue to decline with this bad routine continuously. This study aims to find out the effect of exposure to online games on sleep quality. The research is a cross sectional  research conducted by filling out questionnaires by 81 students and students at SMAN 13 Medan City. The data obtained will be analyzed with Chi-square. Based on data analysis, P=0.004 was obtained where there was a relationship between exposure to online games and sleep quality at SMAN 13 Medan City. There is a significant relationship between exposure to online games and sleep quality at SMAN 13 Medan City.